2015
DOI: 10.1111/jth.13002
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor expressed by circulating cancer cell‐derived microparticles drastically increases the incidence of deep vein thrombosis in mice

Abstract: Background The risk of thrombotic complications such as deep vein thrombosis (DVT) during tumor development is well known. Tumors release into circulation procoagulant microparticles (MPs) that can participate in thrombus formation following vessel injury. The importance of this MP tissue factor (TF) in the initiation of cancer-associated DVT remains uncertain. Objective To address how pancreatic cancer MPs promote DVT in vivo. Methods We combined a DVT mouse model where thrombosis is induced by flow restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 69 publications
5
122
1
3
Order By: Relevance
“…The infused MPs localized to NETs and also expressed P-selectin glycoprotein ligand-1, allowing them to bind to TF and P-selectin presented by endothelial cells and platelets, thereby triggering coagulation. 124 Consistent with these findings, elevated circulating MP levels parallel D-dimers and P-selectin in deep vein thrombosis 125 and are a risk factor for coronary artery disease and atherothrombosis in humans.…”
Section: Microparticlessupporting
confidence: 69%
“…The infused MPs localized to NETs and also expressed P-selectin glycoprotein ligand-1, allowing them to bind to TF and P-selectin presented by endothelial cells and platelets, thereby triggering coagulation. 124 Consistent with these findings, elevated circulating MP levels parallel D-dimers and P-selectin in deep vein thrombosis 125 and are a risk factor for coronary artery disease and atherothrombosis in humans.…”
Section: Microparticlessupporting
confidence: 69%
“…27 It was recently demonstrated that TF-bearing microvesicles derived from pancreatic cancer cells induce deep vein thrombosis (DVT) in mice. 28 Therefore, the interaction of malignant cells with surrounding cells and the coagulation system is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TF, expressed at the cell membrane on most tumors as well as on tumor vasculature and within the tumor microenvironment on stem cells, macrophages, ECs, and myofibroblasts, likely contributes to thrombin production [45][46][47][48][49][50][51]. Tumor microparticles such as exosomes may also display TF and induce thrombin generation [25], as byproducts such as these particles can enter general circulation via the abnormal, leaky blood vessels that are formed during tumor growth [52][53][54]. In addition to tumor cell-associated thrombin production, the components of the endothelium itself, including the endothelial cell protein TM, can regulate thrombin generation/activity to affect the metastatic process [26].…”
Section: Thrombin Generation Within the Host-tumor-environmentmentioning
confidence: 99%